2011
DOI: 10.1002/casp.1082
|View full text |Cite
|
Sign up to set email alerts
|

Familiarity with and social distance from people with mental illness: Testing the mediating effects of prejudiced attitudes

Abstract: The purpose of this study was to examine prejudiced attitudes as a factor associated with social distance from people with mental illness. A total of 289 university students from Greece completed written measures assessing social distance from, prejudiced attitudes about, and familiarity with mental illness. A structural equation model with manifest variables was tested. Participants who reported to be more familiar with mental illness held stronger social care and weaker prejudiced beliefs, and consequently e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 33 publications
3
26
1
2
Order By: Relevance
“…26 These findings were contrary to an Indian study that proved more stigmatizing attitude towards persons with mental illness by the rural participants. 27 In support of earlier research, 28 present study also demonstrated, students those were familiar with people with mental illness hold least restrictive and more benevolent attitudes toward mental illness. Never the less, numerous studies among nursing 29 and medical students 30 revealed that there was a positive change in their attitudes towards persons with mental illness after completion of psychiatry course.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…26 These findings were contrary to an Indian study that proved more stigmatizing attitude towards persons with mental illness by the rural participants. 27 In support of earlier research, 28 present study also demonstrated, students those were familiar with people with mental illness hold least restrictive and more benevolent attitudes toward mental illness. Never the less, numerous studies among nursing 29 and medical students 30 revealed that there was a positive change in their attitudes towards persons with mental illness after completion of psychiatry course.…”
Section: Discussionsupporting
confidence: 88%
“…Ex: "It is not appropriate for a person with mental illness to get married"; (iv) Benevolence (reverse coded): includes eight items (18-23, 25, 26) related to kindness and sympathetic views of the respondents towards people with a mental illness. Ex: "People with mental illness can hold a job"; (v) Pessimistic prediction: composed of four items (27)(28)(29)(30) intended to measure the level of prejudice toward mental illness. Ex: "It is harder for those who have a mental illness to receive the same pay for the same job"; and (vi) Stigmatization: includes four items (31-34) that measure the discriminatory behavior of the students toward mental illness.…”
Section: Methodsmentioning
confidence: 99%
“…The patterns of stigma experiences reported by participants were found to be similar to those cited by other studies done both abroad and locally. Anagnostopoulos and Hantzi (2011) identified four patterns of stigma namely labelling, stereotyping, separating and emotion responses. Expounding of these four patterns, Link and Phelan (2001) stated that the result of such stigma may be self-stigma which may manifest in the form of poor self-image as a result of self-discrimination and isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Students' lack of day-to-day contact with individuals who have been diagnosed with a mental illness may also hinder their desire to work with this population (Eack & Newhill, 2008). Greater familiarity with mental illness corre lates with less need for social distance (Anagnostopoulos & Hantzi, 2011). Corrigan, Edwards, Green, Diwan, and Penn (2001) found that individuals with higher levels of familiarity with men tal illness exhibited lower levels of prejudice toward individuals who were mentally ill. Chung, Chen, and Liu's (2001) findings were consistent with those of Corrigan and colleagues, as their results showed that university students were more inclined to interact with a person identified as mentally ill if the students had had prior contact with individuals with mental illness.…”
Section: Social Work Students and Mental Healthmentioning
confidence: 98%